2000
DOI: 10.1097/00000433-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Baby, a Virus, and a Rat

Abstract: The authors present a case initially thought to be a child abuse homicide that, after complete autopsy and thorough investigation, was determined to be caused by a viral infection and complicated by postmortem animal activity. Neonatal herpes simplex infection and postmortem skin defects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Foul play was suspected at first, but was ruled-out. Another case was reported on the death of an infant who was at first thought by police and emergency physicians to be the victim of child abuse, with the police implicating the single mother; however, autopsy findings, scene investigation, police, and medical examiners communication led to the conclusion that the infant had died of a lung infection, with the "injuries" resulting from postmortem rat activity, thus avoiding wrongful charges and potential conviction of the mother (5). The authors of the current case have recently reviewed and reported on an additional small series of accidental deaths that were originally considered possible homicides (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foul play was suspected at first, but was ruled-out. Another case was reported on the death of an infant who was at first thought by police and emergency physicians to be the victim of child abuse, with the police implicating the single mother; however, autopsy findings, scene investigation, police, and medical examiners communication led to the conclusion that the infant had died of a lung infection, with the "injuries" resulting from postmortem rat activity, thus avoiding wrongful charges and potential conviction of the mother (5). The authors of the current case have recently reviewed and reported on an additional small series of accidental deaths that were originally considered possible homicides (20).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of rigor mortis, the postmortem stiffening of the muscles within the body due to chemical changes in the muscle fibers , and livor mortis, the postmortem settling of blood in the body, can be extremely important when investigating an unwitnessed death, like the case presented. If postmortem skin injuries are produced in portions of the body where lividity is developing or has developed, then the postmortem abrasions are less likely to display the typical yellow appearance and can mimic true injuries . The presence of a distinct, horseshoe‐shaped postmortem abrasion overlying the associated postmortem contusion in the case provides an example of how the two postmortem defects can coexist.…”
Section: Discussionmentioning
confidence: 99%
“…In a like manner, the death investigation community must be watchful for those occasional cases that initially appear to be homicides, but in actuality represent a nonhomicidal manner of death . Such cases can be accidental , suicidal , or even natural . It is well known within the forensic pathology community that all sorts of findings at autopsy can mimic true injuries, and various true injuries are known to occasionally mimic different types of injuries .…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, postmortem animal injuries may raise the possibility of an assault, with genital trauma (74) suggesting ritualistic injuries or rape. Insect and rodent bites have also been confused with child abuse (75,76). Other unusual postmortem injuries may be caused by hamsters, weasels, and birds (77–79).…”
Section: Postmortem Issuesmentioning
confidence: 99%